Actin Cytoskeleton Affects Schwann Cell Migration and Peripheral Nerve Regeneration - Wang, Yaxian; Shan, Qianqian; Pan, Jiacheng; Yi, Sheng (Frontiers in Physiology, 2018)
Actin cytoskeleton regulates many essential biological functions, including cellular development, shape, polarity, and motility. The organization of actin cytoskeleton has also been associated with numerous physiological and pathological conditions, for instance, the elongation of axonal growth cone during peripheral nerve regeneration. However, the spatio-temporal expression patterns of actin cytoskeleton-related genes and the specific roles of actin cytoskeleton following peripheral nerve injury have not been fully revealed. To address this question, we made rat sciatic nerve crush surgery, collected injured sciatic nerve stumps, analyzed RNA deep sequencing outcomes, and specifically studied two significantly involved canonical pathways that were related with actin, actin cytoskeleton signaling and regulation of actin-based motility by Rho. By using bioinformatic tools and qRT-PCR, We identified and validated differentially expressed genes in these two signaling pathways. Moreover, by applying actin polymerization inhibitor cytochalasin D to sciatic nerve crushed rats, we studied the in vivo effect of cytochalasin D and demonstrated that inhibiting actin polymerization would delay the migration of Schwann cells and hinder the repair and regeneration of injured peripheral nerves. Overall, our data revealed the changes of actin cytoskeleton-related genes following peripheral nerve injury and stated the importance of actin cytoskeleton during peripheral nerve regeneration.